STRUCTURAL FUZZY RELIABILITY ANALYSIS USING THE CLASSICAL RELIABILITY THEORY - Nguyen, Tuan; Le, Huynh Xuan (Journal of Applied Engineering Science, 2021)
This study is focused  on a novel approach for calculating structural fuzzy reliability by using the classical reliability theory. In order to handle the structural fuzzy reliability problem, the formulas for establishing normal random variables equivalent to symmetric triangular fuzzy number are presented. From these equivalent random ones, the original problem is converted to the basic structural reliability problems, then the methods of the classical reliability theory should be applied to calculate. Moreover, this study proposes two notions in terms of central fuzzy reliability and standard deviation of fuzzy reliability as well as a calculation procedure to define them. Lastly, the ultimate fuzzy reliability of the proposed method is established and utilized to compare the allowable reliability in the design codes. Numerical results are supervised to verify the accuracy of the proposed method.
Keywords: fuzzy reliability, probability theory, structural reliability, response surface method, energy methods, plastic bending of beams